A novel assessment and treatment approach to patients with Hashimoto's encephalopathy. (27th April 2018) - Laycock, Kate; Chaudhuri, Abhijit; Fuller, Charlotte; Khatami, Zahra; Nkonge, Frederick; Stojanovic, Nemanja
Summary: Hashimoto's encephalopathy (HE) is rarely reported with only a few hundred cases published. Diagnosis is made in patients with an appropriate clinical picture and high antithyroperoxidase (anti-TPO) antibodies after infectious, toxic and metabolic causes of encephalopathy have been excluded. There is little objective data on the neurocognitive impairment in patients with HE and their improvement with treatment. We present the case of a 28-year-old woman with HE. Approach to management was novel as objective neuropsychological assessment was used to assess her clinical condition and response to treatment. Intravenous immunoglobulin (IVIg) as the first-line treatment instead of steroids. She responded well. The case illustrates that a different approach is required for the diagnosis and treatment of HE. A new diagnostic criteria is proposed that includes neurocognitive assessment, serum and CSF antibodies, an abnormal EEG and exclusion of other causes of encephalopathy. Furthermore, treatment should be tailored to the patient. Learning points: Neurocognitive assessment should be carried out to assess the extent of brain involvement in suspected Hashimoto's encephalopathy pre- and post- treatment. Treatment of Hashimoto's encephalopathy should be tailored to the patient. Unifying diagnostic criteria for Hashimoto's encephalopathy must be established.